On C*-Algebras Generated by Deformations of CCR - Kabluchko, Z. A.; Proskurin, D. P.; Samoilenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider C*-algebras generated by deformations of classical commutation relations (CCR), which are generalizations of commutation relations for generalized quons and twisted CCR. We show that the Fock representation is a universal bounded representation. We discuss the connection between the presented deformations and extensions of many-dimensional noncommutative tori.